ANALISIS PENGARUH KUALITAS WEBSITE TERHADAP KEPUASAN PENGGUNA BERDASARKAN METODE WEBQUAL PADA UNIVERSITAS SURABAYA - Ardi Widegdo, Riko Tri; Sulistiowati, Sulistiowati; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
University of Surabaya (Ubaya) uses information technology such as website as information and communication media. Based on data from www.alexa.com, the number of visitors ran kuntil January 2016 is declining until 142.796. University of Surabaya needs to know whether the website quality has satisfied users satisfaction. This study aims to determine the effect of website quality on users satisfaction. The independent variables are usability quality, information quality, and interaction quality. Dependent variable is users satisfaction. The samples used in this study were 125 respondents.Data were analyzed using multiple linear regression analysis. The results showed that usabilty quality has a significant value of 0,000 (<0,05), information quality has a significant value of 0,002 (<0,05), and interaction quality has significant value of 0,011 (<0,05). So that, the conclusion of this study are three independent variables of website quality had statistically significant impact on users satisfaction.